(untitled) (MAGNETON: Jurnal Inovasi Pembelajaran Fisika, 2026)
This study investigates the use of Tracker video analysis as an accessible tool for exploring uniform linear motion (ULM) and uniformly accelerated/decelerated linear motion (UALM) in a resource-limited physics education context in Timor-Leste. Motion experiments were recorded with a smartphone and analyzed using Tracker to obtain position-time and velocity-time data, which were processed in Microsoft Excel for curve fitting and residual inspection. For ULM, the velocity remained approximately constant at v = 1.47 m/s, with apparent acceleration fluctuating around zero due to numerical differentiation. In accelerated UALM, quadratic position time and linear velocity time fits yielded a consistent acceleration of a = 1.68 ± 0.04 m/s² with coefficients of determination R² greater than or equal to 0.93 and relative deviation approximately equal to 1.2%. Decelerated UALM exhibited a small negative acceleration (a = -0.0118 m/s²) with an initial velocity of Vo = 0.54 m/s, producing nearly linear position-time behavior and a residual error of RMSE = 3.88 m. These results demonstrate that Tracker can reliably identify motion types and extract kinematic parameters when combined with external data analysis. Potential pedagogical use is discussed; however, formal learning outcomes were not measured and are recommended for future investigation